CORRUPTION AND ECONOMIC GROWTH IN NIGERIA: DOES DATA SUPPORT “GREASE THE WHEELS” OR “SAND THE WHEELS”? - Felix Odunayo Ajayi; Aduralere Opeyemi Oyelade; Gideon Olugbenga Olanrewaju (Journal of Applied Economics in Developing Countries, 2024)
The study investigated the relationship between corruption and economic growth in Nigeria using data from 1996 to 2020. The research employed the Fully Modified Ordinary Least Squares (FMOLS) method and Granger causality tests. The FMOLS results indicated that both gross fixed capital formation and urbanization significantly and positively influence economic growth in Nigeria, whereas the corruption index has a negative and significant effect, aligning with the "sand the wheels" theory. The Granger causality analysis showed a unidirectional relationship, where gross fixed capital formation Granger-causes GDP growth rate, and GDP growth rate Granger-causes both the corruption index and the relative corruption ranking in Nigeria. Based on these results, the study recommends that policymakers prioritise transparency and good governance by implementing e-governance initiatives to reduce bureaucratic hurdles and opportunities for corruption. Furthermore, there should be consistent monitoring and thorough evaluation of the impact of anti-corruption strategies on economic growth and development to ensure their effectiveness.